Development and Optimization of Oral Dissolution Films for Enhanced Delivery of Ebastine-Loaded Solid Lipid Nanoparticles - Chen K; Sun Y (International Journal of Nanomedicine, 2025)
Kai Chen,1,2 Yong Sun1 1Department of Pharmaceutics, School of Pharmacy, Qingdao University, Qingdao, 266021, People’s Republic of China; 2Pharmacy Department, Affiliated Hospital of Jining Medical University, Jining, 272000, People’s Republic of ChinaCorrespondence: Yong Sun, Email chenkai4230@163.com; sunyong@qdu.edu.cnIntroduction: Approximately 10– 30% of the worldwide population suffers from allergic diseases. Although ebastine (EBT) is described as a potential treatment for allergies, its effects are compromised due to poor solubility and low bioavailability.Methods: This study introduced a novel delivery platform for ebastine by combining solid lipid nanoparticles (SLNs) with oral dissolution films (ODFs). Ebastine SLNs were fabricated using hot melt and ultrasonic emulsification methods, and the SLNs’ formulation was optimized by a central composite rotatable design. The developed SLNs were further introduced into a mixed polymer solution of PVA and HPMC to prepare ODFs using the solvent casting method.Results: The optimized EBT-SLNs with spherical structures demonstrated nanoparticle size (147.5 ± 3.32 nm), low polydispersity index (PDI, 0.106 ± 0.005), high entrapment efficiency (86.7%), as well as drug loading (10.02%), respectively. The optimum formulation of ODFs was composed of equal proportion of HPMC and PVA according to normalization methods by evaluation of physicochemical properties including physical appearance, folding endurance and disintegration time. Scanning electron microscopy results disclosed that EBT-SLNs were confined within the network of ODFs and no aggregation SLNs was found. Reconstitution experiments showed EBT-SLNs were still within the nanometers range and maintained a homogenous state, suggesting that incorporation of SLNs into ODFs not compromised their nanoparticulate properties. The in vitro drug release patterns from ODFs containing EBT-SLNs exhibited a fast release profile compared to the commercial EBT tablets.Discussion: The developed system demonstrates enhanced solubility, stability, and bioavailability of ebastine, offering a promising alternative to traditional oral tablets, with potential advantages in patient compliance and rapid drug onset. Therefore, the ODFs containing SLNs can be considered as an efficient approach for EBT administration. Keywords: ebastine, solid lipid nanoparticles, oral dissolution films, central composite rotatable design